Understanding Gender Equality In The Perspective Of Surah Al-Hujurat Verse 13 And Bukhari Hadith No. 4787 - Syifa, Nadia; Zakiyah, Ermita; Fattah, Abdul (International Conference on Law, Technology, Spirituality and Society (ICOLESS); Vol 3 (2023): The 6th International Conference on Law, Technology, Spirituality and Society (ICOLESS), 2023)
The purpose of writing this article is to answer from the perspective of the Quran and Hadith regarding the position of women in their understanding of gender. Islam distinguishes the position between men and women, as if patriarchal culture is a religious teaching that must be believed and must be practiced in life. So, women come in second position in society. There are many studies on gender in terms of social and culture that women have the same position as men. However, no one discusses the perspective of answers from the Quran and Hadith. The results of this research are how the study of verses of the Quran regarding gender equality and the validity of these hadiths can be used as a legal basis.